2007
DOI: 10.1038/sj.eye.6702890
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial studying neuroprotection in low-pressure glaucoma

Abstract: The Low-Pressure Glaucoma Treatment Study is a double-masked, randomized trial comparing the visual outcomes of 190 low-pressure glaucoma patients randomized to intraocular pressure reduction with brimonidine tartrate or timolol maleate. Baseline characteristics of participants are compared to published studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Previously, only studies with a minimum of five years follow up were eligible for this review. One of the studies identified from the original electronic searches in 2010 became eligible based on the change to four years follow up (LoGTS 2011). Of the 655 new records identified, we excluded 638 by screening titles and abstracts and 17 were further reviewed by the full text.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, only studies with a minimum of five years follow up were eligible for this review. One of the studies identified from the original electronic searches in 2010 became eligible based on the change to four years follow up (LoGTS 2011). Of the 655 new records identified, we excluded 638 by screening titles and abstracts and 17 were further reviewed by the full text.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 full text articles reviewed, we excluded 14 and included three in the review. These three records included in the review all reported one study, LoGTS 2011.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations